2016
DOI: 10.21704/rea.v4i1-2.297
|View full text |Cite
|
Sign up to set email alerts
|

CAPACIDAD DEL Rhizobium DE PROMOVER EL CRECIMIENTO EN PLANTAS DE TOMATE (Lycopersicon esculentum Miller

Abstract: ResumenEl presente estudio se realizó con el objetivo de evaluar el efecto de 19 cepas de Rhizobium en la germinación y en el crecimiento de plantas de Lycopersicon esculentum. El efecto de los rizobios sobre la germinación de las semillas se determinó inoculando las semillas con suspensiones densas de rizobio y dejándolas germinar en arena esterilizada. El efecto sobre el crecimiento del cultivo se estudió en condiciones de cámara de crecimiento, utilizando suelo franco arenoso, con pH 7.3. El diseño utilizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
0
9
0
11
Order By: Relevance
“…The results coincide with those reported by other authors who demonstrated the positive effect of inoculation of tomato plants with strains of Bacillus (Lagunas et al, 2001;Luna Martinez et al, 2013. ) And other bacterial genera such as Azospirillum (Terry-Alfonso et al, 2005), Pseudomonas (Gravel et al, 2007) and Rhizobium (Santillana et al, 2005). This behavior could be related to the production of metabolites of IAA type by the inoculated strain.…”
Section: Effect Of Bacillus Subtilis Strain Gibi 200 On Tomato Cropmentioning
confidence: 99%
See 1 more Smart Citation
“…The results coincide with those reported by other authors who demonstrated the positive effect of inoculation of tomato plants with strains of Bacillus (Lagunas et al, 2001;Luna Martinez et al, 2013. ) And other bacterial genera such as Azospirillum (Terry-Alfonso et al, 2005), Pseudomonas (Gravel et al, 2007) and Rhizobium (Santillana et al, 2005). This behavior could be related to the production of metabolites of IAA type by the inoculated strain.…”
Section: Effect Of Bacillus Subtilis Strain Gibi 200 On Tomato Cropmentioning
confidence: 99%
“…This behavior could be related to the production of metabolites of IAA type by the inoculated strain. The IAA induces plant growth by increasing cell division and differentiation of tissue, effects that are reflected in a higher content of biomass (Lagunas et al, 2001;Santillana et al, 2005). It has also been argued that the IAA absorbed by the seeds and roots of plants could stimulate the activity of the ACC synthase enzyme, which is involved in the synthesis of ethylene.…”
Section: Effect Of Bacillus Subtilis Strain Gibi 200 On Tomato Cropmentioning
confidence: 99%
“…for the biological inoculant production is an economic and ecological alternative to ensure and recover the productivity of the soils, reducing the indiscriminate use of chemical fertilizers. This rhizobacteria, in addition to fixing nitrogen produce phytohormones, participate in the solubilization of phosphorus and antagonistic reaction, allowing a greater productivity of the host legume plant in any type of soil (Akhtar and Siddiqui, 2009;Santillana et al, 2005;Mourad et al, 2009;Bardin et al, 2004;Puertas et al, 2006;Ahemad andKibret, 2014, Mabrouk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Los biofertilizantes no tienen un efecto contaminante sobre el suelo ya que los microorganismos contenidos en estos se utilizan para aumentar la disponibilidad de algunos nutrientes cómo el P que es de baja disponibilidad (Ohtomo y Saito, 2005), fijar nitrógeno y aumentar la disponibilidad de nitrógeno en hortalizas, como tomate (Santillana et al, 2005) y cebolla (Balemi et al, 2007), y ofrecer a la raíz protección contra patógenos (Morales-Ibarra, 2009).…”
Section: Introductionunclassified